Evaluating estuarine nursery use and life history patterns of Pomatomus saltatrix in eastern Australia - Schilling, HT (2018)
Estuaries provide important nursery habitats for juvenile fish, but many species move between estuarine and coastal habitats throughout their life. We used otolith chemistry to evaluate the use of estuaries and the coastal marine environment by juvenile Pomatomus saltatrix in eastern Australia. Otolith chemical signatures of juveniles from 12 estuaries, spanning 10° of latitude, were characterised using laser ablation-inductively coupled plasma-mass spectrometry. Based upon multivariate otolith elemental signatures, fish collected from most estuaries could not be successfully discriminated from one another. This was attributed to the varying influence of marine water on otolith elemental composition in fish from all estuaries. Using a reduced number of estuarine groups, the multivariate juvenile otolith elemental signatures and univariate Sr:Ca ratio suggest that between 24 and 52% of adult P. saltatrix had a juvenile period influenced by the marine environment. Elemental profiles across adult (age-1) otoliths highlighted a variety of life history patterns, not all consistent with a juvenile estuarine phase. Furthermore, the presence of age-0 juveniles in coastal waters was confirmed from historical length-frequency data from coastal trawls. Combining multiple lines of evidence suggests considerable plasticity in juvenile life history for P. saltatrix in eastern Australia through their utilisation of both estuarine and coastal nurseries. Knowledge of juvenile life history is important for the management of coastal species of commercial and recreational importance such as P. saltatrix.